Occurrence and Type of Adverse Events During the Use of Stationary Gait Robots—A Systematic Literature Review - Bessler, Jule; Prange-Lasonder, Gerdienke B.; Schulte, Robert V.; Schaake, Leendert; Prinsen, Erik C.; Buurke, Jaap H. (Frontiers in Robotics and AI, 2020)
Robot-assisted gait training (RAGT) devices are used in rehabilitation to improve patients’ walking function. While there are some reports on adverse events and associated risks in overground exoskeletons, the risks of stationary gait trainers cannot be accurately assessed. We therefore aimed to collect information on adverse events occurring during use of stationary gait robots and identify associated risks as well as gaps and needs for safe use of these devices. We searched both bibliographic and full-text literature databases for peer-reviewed articles describing outcomes of stationary RAGT and specifically mentioning adverse events. We then compiled information on occurrence and types of adverse events and on the quality of adverse event reporting. Based on this, we analyzed risks of RAGT in stationary gait robots. We included 50 studies involving 985 subjects and found reports of adverse events in 18 of those studies. Many of the adverse event reports were incomplete or did not include sufficient detail on aspects like severity or patient characteristics, which hinders precise counts of adverse event related information. Over 169 device-related adverse events experienced by between 79 and 124 patients were reported. Soft tissue related adverse events occurred most frequently and were mostly reported in end-effector type devices. Musculoskeletal adverse events had the second highest prevalence and occurred mainly in exoskeleton type devices. We further identified physiological adverse events including blood pressure changes which occurred in both exoskeleton type and end-effector type devices. Training in stationary gait robots can cause injuries or discomfort to skin, underlying tissue and the musculoskeletal system as well as unwanted blood pressure changes. The underlying risks for the most prevalent injury types include excessive pressure and shear at the interface between robot and human (cuffs/harness), as well as increased moments and forces applied to the musculoskeletal system likely caused by misalignments (between joint axes of robot and human). There is a need for more structured and complete recording and dissemination of adverse events related to robotic gait training to increase knowledge on risks. With this information, appropriate mitigation strategies can and should be developed and implemented in RAGT devices, to increase their safety.